Dynamic BH3 profiling method for rapid identification of active therapy in BH3 mimetics resistant xenograft mouse models - Olesinski, Elyse A. (STAR Protoc, 2021)
The clinical effectiveness of BH3 mimetics therapy is limited by the inevitable emergence of acquired resistance. We present a protocol to model in vivo acquired resistance to BH3 mimetics in patient-derived xenograft (PDX) mouse models of acute myeloid leukemia. Using resistant PDXs as a valuable model, we next introduce a protocol for dynamic BH3 profiling (DBP) method. DBP allows functional identification of effective drug therapies based on measurements of drug-induced apoptosis signaling to overcome in vivo BH3 mimetics resistance. For complete details on the use and execution of this protocol, please refer to Bhatt et al. (2020).